Application and Benefits of Self-Activated Phthalocyanine in Dentistry: An Integrative Review (Revista Brasileira Multidisciplinar, 2025)
The objective of this study was to conduct an integrative literature review regarding the properties of Phthalocyanines and the benefits of their application in dentistry. A bibliographic search was conducted using the MEDLINE/PubMed database for the period from 2020 to 2022. The search terms used were "phthalocyanine" AND "dentistry." A total of 8 articles were included in the review. In vitro and in vivo studies demonstrated the self-activated phthalocyanine with potential antibacterial, antifungal, antibiofilm, antiviral effects, non-cytotoxic characteristics, and positive effects in complementary therapy for periodontal disease and tissue repair. Phthalocyanine exhibits excellent antimicrobial properties against bacteria, fungi, and viruses, along with low cytotoxicity, showing promising results in wound healing processes. It can be considered a suitable chemical agent for post-operative control.
Keywords: Phthalocyanine; Periodontal disease; Tissue repair; Self-activated phthalocyanine